Flamenco as an educational tool in the academic curriculum: Strengthening the sense of community and Andalusian identity - Heredia-Carroza, Jesús; López-Ruiz, Carmen; Carrosa-Zayas, Ángeles; Chavarría-Ortiz, Carlos; Palma-Martos, Luis Antonio (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2025)
This study examines future teachers’ perceptions of incorporating flamenco into the Andalusian educational curriculum and its potential impact on fostering a sense of community and Andalusian identity. The study analysed 301 surveys conducted among university students enrolled in academic education programs. Descriptive statistical analysis revealed that 88.4% of participants supported the integration of formal flamenco in schools. A more detailed analysis of the responses revealed recognition of the influence of flamenco on various aspects such as the preservation of heritage (5.29), a sense of belonging to a community (5.15) and cultural identity (5.17), which guarantees a lasting source of inspiration and growth for future generations. Flamenco is not only considered a cultural relic but a vital part of Andalusia's heritage, essential to its future.